D ATA PROCESSING PIPELINE FOR DECAMETER PULSAR/TRANSIENT SURVEY - Vasylieva, I. Y.; Zakharenko, V. V.; Zarka, P.; Ulyanov, O. M.; Shevtsova, A. I.; Seredkina, A. A. (Одеські астрономічні публікації, 2013)
The study of the low-frequency radio sky at short time scales provides the insights into the nature of transient radio sources as well as gives a sensitive tool for interstellar medium sensing. The decameter survey of the northern sky is aimed to discover new sources of transient and repetitive emission within more than 100 Tb of the high time resolution data. The efficient pipeline of data cleaning and processing is developed and successfully tested.